To Consolidate or Not to Consolidate? A Multi-Step Analysis to Assess Needed Fiscal Sustainability - António Afonso; José Alves; Jo\~ao Tovar Jalles (Center for Economic Studies and ifo Institute (CESifo), 2022)
We assess the specific need (or its absence) of a country to implement a fiscal consolidation programme by focusing specifically on their degree of success, notably in terms of fiscal sustainability. The "need" to consolidate is based on having a primary balance above or below the debt-stabilizing primary balance (provided by the IMF's Debt Sustainability Analysis) for each country. We then link the need for and the actual (historical) existence of fiscal adjustments to their sustainability impact. Looking at a large sample of developed and developing economics over the period 1980-2018, we find that, on average, there is a higher need of consolidations in advanced economies than in developing economies. In addition, the implementation of a fiscal consolidation program implies an improvement in the degree of public finances sustainability, for in advanced and developing economies. Finally, fiscal sustainability deteriorates when the need to implement a fiscal retrenchment arises.
Keywords: C23; E21; E62; H50; H62; 330; fiscal consolidation; cyclically-adjusted primary balance; sustainability; panel data; time-varying